2019
DOI: 10.1016/j.jobcr.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic treatment of class three malocclusion using clear aligners: A case report

Abstract: Class III malocclusion is a growth-related challenging condition for orthodontists. We present a case of a 11-yearold girl with a skeletal class III malocclusion with bilateral cross bite, and a functional shift of the lower dental midline. A multiphase clear aligners' treatment was scheduled with the aim of removing all dental interferences which involved an anterior displacement of the mandible. At one-year follow-up, clear aligners' therapy resulted in skeletal and dental improvements. Clear aligners therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 9 publications
0
14
0
10
Order By: Relevance
“…Another limitation is related to the effectiveness and predictability of conservative treatment with functional appliances, which is dependent on patients’ compliance, self-motivation, peer and authority influence, quality of life impairment and adaptability, perceived treatment progress, as well as pragmatic and recall issues, which may reduce or decrease the wearing time of the oral appliances [ 43 , 44 ]. Patient recommendations to improve compliance included effective communication, tailoring of prescribed wear duration, physical alteration of the appliance, and use of reminding tools [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is related to the effectiveness and predictability of conservative treatment with functional appliances, which is dependent on patients’ compliance, self-motivation, peer and authority influence, quality of life impairment and adaptability, perceived treatment progress, as well as pragmatic and recall issues, which may reduce or decrease the wearing time of the oral appliances [ 43 , 44 ]. Patient recommendations to improve compliance included effective communication, tailoring of prescribed wear duration, physical alteration of the appliance, and use of reminding tools [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In surgical cases, clear aligners have been successfully used for the correction of the skeletal Class III jaw relationship in adults by surgery first then clear aligners were used to finish the patient’s occlusion [ 3 , 4 , 5 ]. Extraction of lower incisor also has long been reported to be an acceptable treatment approach in Class III malocclusion cases especially in adults [ 6 , 7 , 8 ]. The use of high frequency vibration (HFV) has been introduced in orthodontics and recent reports showed that it does not only accelerate tooth movement, but also it increases bone density at the end of active treatment in human as well as after extraction in rats [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study highlights the pharyngeal airway volume was significantly correlated with craniofacial parameters, thus highlighting the association between form and function. There is also a strong interaction between craniofacial morphology, obesity, hypertension, ageing and breathing disorders such as OSAS [ 33 , 34 , 35 ]. Clinically, most of the essential parameters that are usually modified or modulated during orthodontic/orthopaedic/orthognathic treatment have been selected so as to get a better understanding if any relation exists directly or indirectly with the airway volumes.…”
Section: Discussionmentioning
confidence: 99%